A Facile Synthesis of Flower-shaped ZnO/Reduced Graphene Oxide Microsphere Composites for Photocatalytic Degradation of Methyl Orange - Zhu, Guang; Chen, Liangwei; Wei, Qiang; Guo, Peijun; Li, Xuelian; Wang, Wenqi; Luo, Peng; Wang, Hongyan; Zhang, Li (Current Nanoscience, 2016)
Flower-shaped ZnO/reduced graphene oxide (RGO) microsphere composites were successfully fabricated via a facile hydrothermal treatment of the aqueous solution containing graphene oxide and ZnO microspheres, and their photocatalytic performance in degradation of methyl orange (MO) was investigated. The results indicated that ZnO/RGO microsphere composites with 3 wt.% GO achieves a maximum MO degradation efficiency of 88% under ultraviolet light irradiation for 140 min, compared with pure ZnO microspheres (78%). The improved photocatalytic performance can be attributed to the suppression of charge carriers recombination resulting from the interaction between ZnO and RGO.
Keywords: ZnO